2020
DOI: 10.2196/18189
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence for Caregivers of Persons With Alzheimer’s Disease and Related Dementias: Systematic Literature Review

et al.

Abstract: Background Artificial intelligence (AI) has great potential for improving the care of persons with Alzheimer’s disease and related dementias (ADRD) and the quality of life of their family caregivers. To date, however, systematic review of the literature on the impact of AI on ADRD management has been lacking. Objective This paper aims to (1) identify and examine literature on AI that provides information to facilitate ADRD management by caregivers of in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 53 publications
3
33
0
1
Order By: Relevance
“…The ultimate goal of artificial intelligence is to construct machines that process information intelligently in the same way that people do [ 5 ]. Intelligent agents are another title for these technologies [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ultimate goal of artificial intelligence is to construct machines that process information intelligently in the same way that people do [ 5 ]. Intelligent agents are another title for these technologies [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…AI technologies may better prepare and support caregivers in their tasks. A systematic review of 30 studies ( 40 ) described a range of assistive AI devices designed to facilitate caregiving, such as support with dressing or handwashing or detecting falls. However, the review noted that most studies were descriptive or exploratory, offering very limited evidence of such technology to date.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…The empirical approaches familiar to clinicians—namely hypothesis testing and reliance on evidence-based practice—are potentially at odds with the proof-of-concept, hypothesis-generating demonstrations that characterize much AI research to date. The innovations propelling AI forward are often tested on small samples to demonstrate proof-of-concept ( 40 ); however, this runs the risk that ML models will be overfit, leading to spurious findings and lacking generalizability to new data sources. External validation of the model (that is, testing in new datasets) is essential to improve prediction, yet only three of 51 studies in a recent review of ML in psychotherapy research did so ( 45 ).…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other systematic reviews on virtual agents in health care revealed that the number of experiments with voice-enabled agents was rather limited. Xie et al [ 12 ] conducted a review on AI specifically for caregivers of persons with dementia, but did not report on any virtual agents for which an actual experiment had been conducted. Schachner et al [ 13 ] reviewed papers on AI-based conversational agents for chronic conditions.…”
Section: Introductionmentioning
confidence: 99%